Rising seas and sinking islands: the geopolitics of climate change in Tuvalu and Kiribati - Saddington, LR (2021)
Anthropogenic climate change is predicted to accelerate throughout the 21st century, with transformative impacts for biophysical and social systems. Due to their vulnerability to sea level rise and because of fears that they may be fully inundated, low-lying atoll states have been framed as spaces at the forefront of climate change. Questions have been raised over the future sovereignty, territorial integrity and identity of these states in a warmer and wetter world. This thesis explores climate change in relation to small island states from a critical geopolitics perspective by focusing on two Pacific atoll states: Tuvalu and Kiribati. It examines how space and time are influencing understandings of climate change within these states in relation to geopolitics, adaptation and diplomacy. Whilst geomorphologically similar, the perceived threat from climate change has been constructed, and responded to, differently in Tuvalu and Kiribati.